Differential expression of extracellular matrix components in the Fallopian tubes throughout the menstrual cycle - Diaz Patricia S; Solar Paula A; Juica Natalia E; Orihuela Pedro A; Cardenas Hugo; Christodoulides Myron; Vargas Renato; Velasquez Luis A (BMC, 2012)
Abstract Background One of the unique characteristics of the female genital tract is the extensive tissue remodeling observed throughout the menstrual cycle. Multiple components of the extracellular matrix take part in this tissue rebuilding; however, the individual components involved have not been identified. Methods In the present study, the expression of extracellular matrix proteins and selected matrix metalloproteinase (MMP) activities in Fallopian tubes (FT) throughout the menstrual cycle were examined by PCR array, immunocytochemistry, zymography and bioinformatics. Results Of the eighty-four genes analyzed, eighty-three were expressed in the FT during at least one stage of the menstrual cycle. We observed a significant increase (>/=2-fold) in ADAMTS1, ADAMTS13, COL7A1, MMP3, MMP9, PECAM1, and THBS3 in the periovulatory phase compared to the follicular phase. Meanwhile, we observed a significant decrease (>/= 2-fold) in COL7A1, ICAM1, ITGA8, MMP16, MMP9, CLEC3B, SELE and TIMP2 in the lutheal phase compared to the periovulatory phase. Immunocytochemistry showed that MMP-3 and MMP-9 were localized in the endosalpinx during all phases of the menstrual cycle. Gelatin zymograms detected non-cycle-dependent protease activity. Conclusions Several extracellular matrix components were regulated throughout the menstrual cycle in a cyclic pattern, suggesting a possible steroid regulation and a role in tissue remodeling and FT functions.